Slant submersions from almost paracontact Riemannian manifolds - GÜNDÜZALP, YILMAZ (Kuwait Journal of Science, 2015)
In this paper, we introduce slant submersions from almost paracontact Riemannian manifoldsonto Riemannian manifolds. We give examples and investigate the geometry of foliationswhich are arisen from the definition of a Riemannian submersion. We also find necessary andsufficient conditions for a slant submersion to be totally geodesic.